(untitled) (Biological Sciences - PJSIR, 2002)
Inter-comparison of DC voltage standards has now become the most suitable and authenticated means for maintaining the international tractability of national standards all over the world. The results of an intercomparison on DC voltage standards carried out at National Physical & Standards Laboratory (NPSL) Islamabad are presented and discussed.